MODELAGEM MATEMÁTICA NO PROCESSO DE SECAGEM DE GRÃOS ATRAVÉS DE DADOS EXPERIMENTAIS COM CAMADAS FINAS - Zucolotto, Benjamim; Khatchatourian, Oleg; Oliveira, Fabiane A. d. (Salão do Conhecimento, 2013)
Resumo